2021
DOI: 10.1371/journal.pone.0251624
|View full text |Cite
|
Sign up to set email alerts
|

Modelling geographical accessibility to urban centres in Kenya in 2019

Abstract: Background Access to major services, often located in urban centres, is key to the realisation of numerous Sustainable Development Goals (SDGs). In Kenya, there are no up-to-date and localised estimates of spatial access to urban centres. We estimate the travel time to urban centres and identify marginalised populations for prioritisation and targeting. Methods Urban centres were mapped from the 2019 Kenya population census and combined with spatial databases of road networks, elevation, land use and travel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 70 publications
(158 reference statements)
0
18
0
Order By: Relevance
“…Vaccination coverage in urban areas was higher by 27.8% as compared to rural areas. There are several reasons for higher coverages in urban areas, including but not limited to shorter travel times also reported in other studies [54] , [55] , increased availability of vaccines, higher literacy [23] , [24] , occupation [23] , [24] , [25] , [26] , and low hesitancy rates [5] . Despite the higher rates of vaccination coverage in urban areas, it is projected to reach 73.75% in Nairobi and 44.56% in Mombasa by March 2022.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…Vaccination coverage in urban areas was higher by 27.8% as compared to rural areas. There are several reasons for higher coverages in urban areas, including but not limited to shorter travel times also reported in other studies [54] , [55] , increased availability of vaccines, higher literacy [23] , [24] , occupation [23] , [24] , [25] , [26] , and low hesitancy rates [5] . Despite the higher rates of vaccination coverage in urban areas, it is projected to reach 73.75% in Nairobi and 44.56% in Mombasa by March 2022.…”
Section: Discussionmentioning
confidence: 75%
“…Fine-scale mapping could refine geographical targeting to reach physically marginalized population. The effect of travel time to the nearest vaccination site was not assessed for changing road conditions in rural areas, effects of by-passing due to vaccine stock-outs [54] , [55] and perceived quality of services offered by the vaccination site [84] . Previous studies that examined changing road conditions showed longer journeys during wet seasons as compared to drier seasons [62] , [85] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations